Ҳисоб кунед:
\(\frac{a+b}{a-b}\), агар \(a^2+b^2=3ab\) ва 0 \(\lt b\lt a\) бошад.
Бигзор a=kb, дар ин ҷо k>1.
\(a^2+b^2=3ab\)
\(\frac{1}{b^2}\cdot(a^2+b^2)=\frac{1}{b^2}\cdot3ab\)
\(\frac{a^2}{b^2}+1=3\cdot{a}{b}\)
\(k=\frac{a}{b}\)
\(k^2+1=3\cdot k\)
\(k^2-3k+1=0\)
\(D=9-4=5\)
\(k_1=\frac{3+\sqrt{5}}{2}\)
\(k_2=\frac{3-\sqrt{5}}{2}\)
Азбаски k>1, \(k=\frac{3+\sqrt{5}}{2}\)
\(\frac{a+b}{a-b}=\frac{\frac{1}{b}\cdot(a+b)}{\frac{1}{b}\cdot(a-b)}=\)
\(=\frac{\frac{a}{b}+1}{\frac{a}{b}-1}=\)
\(=\frac{k+1}{k-1}=\frac{\frac{3+\sqrt{5}}{2}+1}{\frac{3+\sqrt{5}}{2}-1}=\)
\(=\frac{5+\sqrt{5}}{1+\sqrt{5}}=\frac{\sqrt{5}\cdot(\sqrt{5}+1}{1+\sqrt{5}}=\)
\(=\sqrt{5}\)
\(\frac{a+b}{a-b}=\sqrt{5}\)
Ҷавоб: \(\sqrt{5}\)